Land degradation: A challenge to Ethiopia - Taddese, G. (Springer, 2001)
Land degradation is a great threat for the future and it requires great effort and resources to ameliorate. The major causes of land degradation in Ethiopia are the rapid population increase, severe soil loss, deforestation, low vegetative cover and unbalanced crop and livestock production. Inappropriate land-use systems and land-tenure policies enhance desertification and loss of agrobiodiversity. Utilization of dung and crop residues for fuel and other uses disturbs the sustainability of land resources. The supply of inputs such as fertilizer, farm machinery and credits are very low. The balance between crop, livestock, and forest production is disturbed, and the farmer is forced to put more land into crop production. For environmentally and socially sustainable development, there is an urgent need to promote awareness and understanding of the interdependence of natural, socioeconomic, and political systems at local and national levels. Understanding the current status and causes of land degradation is very important. This paper reveals the important elements of land degradation in Ethiopia and suggests possible solutions that may help to ameliorate the situation.